Can Lessons for Climate Change Adaptation Be Taken From One Continent To Another? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Roberto Quiroz from CIP (International Potato Centre). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya